2017
DOI: 10.1186/s12906-017-1642-2
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Effect of catalpol on remyelination through experimental autoimmune encephalomyelitis acting to promote Olig1 and Olig2 expressions in mice

Abstract: BackgroundMultiple sclerosis (MS) as an autoimmune disorder is a common disease occurring in central nervous system (CNS) and the remyelination plays a pivotal role in the alleviating neurological impairment in the MS. Catalpol, an effective component extracted from the Chinese herb Radix Rehmanniae, which has been proved protective in cerebral diseases.MethodsTo determine the protective effects and mechanisms of Catalpol on MS, the mice with experimental autoimmune encephalomyelitis (EAE) were induced by myel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…In vitro, BSYSC-containing serum also increased the proliferation, migration, and differentiation of OPCs, suggesting that BSYSC promotes remyelination. In previous in vivo and in vitro studies, BSYSC has been shown to be able to upregulate myelin-related molecules, such as Olig1, Olig2/Brdu, PDGFR α , and CNPase in the brain tissue of EAE mice [ 26 , 29 ]. Catalpol, the active ingredient of Rehmanniae Radix (Dihuang) in BSYSC, regulates the transcription factors Olig1 and Olig2 in OPCs [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, BSYSC-containing serum also increased the proliferation, migration, and differentiation of OPCs, suggesting that BSYSC promotes remyelination. In previous in vivo and in vitro studies, BSYSC has been shown to be able to upregulate myelin-related molecules, such as Olig1, Olig2/Brdu, PDGFR α , and CNPase in the brain tissue of EAE mice [ 26 , 29 ]. Catalpol, the active ingredient of Rehmanniae Radix (Dihuang) in BSYSC, regulates the transcription factors Olig1 and Olig2 in OPCs [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Catalpol and harpagide are two characteristic iridoid glycosides extensively investigated in Zeng Ye Decoction. Catalpol is now expanding rapidly and making its way to the forefront of anti-diabetic [2] [3] [4], anti-inflammatory [5] [6] [7] and neuroprotective research [8] [9] [10] [11]. Harpagide has also presented anti-inflammatory, anti-osteoporotic and antibacterial activities [12] [13] [14].…”
Section: Introductionmentioning
confidence: 99%
“…Total 24 compounds were identified. Particularly, Catalpol showed to ameliorate pathological process of EAE mice (Yang et al, 2017 ; Li et al, 2018 ). Thus, we quantitatively detected the content of Catalpol as mark compound for quality control.…”
Section: Discussionmentioning
confidence: 99%
“…Catalpol attenuated cognitive impairment and protected hippocampal CA1 region neuronal cell death from oxidative/nitrative injury (Li et al, 2004 , 2005 ). Catalpol treatment ameliorated the pathogenesis of EAE (Yang et al, 2017 ; Li et al, 2018 ). Thus, we used Catalpol as bioactive mark compound for the quality control of the RR extract.…”
Section: Discussionmentioning
confidence: 99%